Perennialization and Cover Cropping Mitigate Soil Carbon Loss from Residue Harvesting. Issue 4 (1st July 2018) - Jones, Curtis D.; Oates, Lawrence G.; Robertson, G. Philip; Izaurralde, R. Cesar
Abstract : While the US Midwest is expected to serve as a primary feedstock source for cellulosic biofuel production, the impacts of residue harvesting on soil organic carbon (SOC) may greatly limit sustainable production capacity. However, viable feedstock production could be realized through adoption of management practices and cropping systems that offset residue‐harvest‐induced SOC losses. Sequestration of SOC can be enhanced by increasing the duration of crop soil cover through cover or double cropping or cultivation of dedicated perennials. However, assessing the efficacy of such options across sites and over long periods is experimentally challenging. Hence, we use the Environmental Productivity Integrated Climate (EPIC) model to provide such an assessment. Model‐data integration was used to calibrate and evaluate model suitability, which exhibited reasonable effectiveness through R 2 of 0.97 and 0.63 for SOC stock and yield, respectively. Long‐term simulations indicate considerable capacity for offsetting SOC loss. Incorporating rye ( Secale cereal L.) into continuous corn ( Zea mays L.) and corn–soybean [ Glycine max (L.) Merr.] systems offset the SOC losses induced by harvesting 21.2 and 38.3% of available stover, respectively. Similarly, converting 20.4% of corn–soybean land to miscanthus ( Miscanthus × giganteus J.M. Greef & Deuter ex Hodkinson & Renvoize) or 27.5% of land to switchgrass ( Panicum virgatum L.) offset the SOC impacts of harvesting 60% of stover from the remaining corn–soybean lands. These responses indicate that adoption of such measures would sizably affect the life cycle consequences of residue‐derived biofuels and expand estimates of sustainable cellulosic feedstock production capacity from the US Midwest. Core Ideas: EPIC suitably assessed SOC under annual, cover, double, and perennial crops. Perennial cultivation offset the SOC losses of considerable residue harvesting. Rye double crops offset sizable residue‐induced SOC losses. Adoption could greatly expand Midwestern sustainable biofuel production capacity.